Comparison of the knowledge level of individuals living in rural and urban areas about skin cancer and sun protection - Erdogan, Elif; Toraman, Aynur Uysal (International Journal Of Community Medicine And Public Health, 2021)
Background: Among the types of cancer, skin cancer stands out due to its increasing incidence rate both in Turkey and around the world. This study was conducted to compare the knowledge level of the people living in rural and urban areas about skin cancer and sun protection. Methods: The study was conducted with 384 people living in Kirazlı village (rural area) and Türkmen district (urban area) in Kuşadası. Kuşadası town is located in Turkey's western region. Individual’s skin cancer and sun protection knowledge levels were evaluated with Skin Cancer and Sun Knowledge Scale consisting of 25 items. Results: As a result of this evaluation, the median values were 12.5 for the people living in rural areas and 15 for the people living in urban areas. It was found that there was a statistically meaningful difference between skin cancer and sun knowledge scale points of the people living in rural and urban areas (U=9419.5, p<0.01). Conclusions: This study concludes that individuals from urban populations were more knowledgeable than the ones from rural populations in the field of skin cancer and the sun protection behavior.